Clinicopathological Characteristics and Predictive Clinical Features of Lacrimal Gland Lesions - Eriska, Yossi; Raja Erinda; Trilaksana Nugroho (Majalah Oftalmologi Indonesia, 2026)
Introduction: Lacrimal gland tumors encompass a wide spectrum of benign, malignant and inflammatory conditions. Understanding the clinico-demographic profile and histopathological findings is crucial for early detection, determining appropriate treatment strategies and improving patient outcomes. Methods: This was a retrospective observational study of patient with lacrimal gland lesions diagnosed at the Reconstructive Oculoplastic and Oncology department at a tertiary care hospital in Central Java. Thirty-nine patients with biopsy-proven lesions between January 2021 and December 2024 were included. Clinical characteristics including age, sex, laterality, symptom duration, proptosis, lagophthalmos, and ocular motility restriction were evaluated. Histopathological diagnoses were categorized into benign, malignant, and inflammatory lesions. Statistical analyses were performed to assess associations between clinical variables, sex, and tumor classification. Results: A total 47 eyes of 39 patients were retrospectively reviewed. The mean age of patients was 46.15 ± 20.27 years (range 2–76), with 48.7% male and 51.3% female. Malignant tumors were more frequent in patients older than 60 years (69.2%), while benign tumors were more common in patients aged 40–59 years (60.0%). Histopathological analysis demonstrated that lymphoid and inflammatory disorders were the most common lesions. Inflammatory disorders consisted of dacryoadenitis and systemic inflammatory disease (sarcoidosis). Proptosis and shorter symptom duration were significantly associated with malignancy, whereas bilateral involvement was significantly associated with inflammatory disorders. No statistically significant difference in tumor classification was observed between male and female patients. Conclusion: Lymphoid and inflammatory disorders were the most prevalent lacrimal gland lesions. Identifying clinical markers such as proptosis, symptom duration, laterality can assist in early malignancy detection and guide management decisions effectively. This study is limited by its retrospective design, single-center setting, and small sample size, which may introduce selection bias and limit generaizability.